Associations between systemic inflammatory indices and the risk of renal function decline in patients with type 2 diabetes mellitus: a retrospective cohort study - Shang, Zhi; Zhang, Hai-Dong; Qian, Hui; Gao, Yue-Ming; Feng, Song-Tao (Frontiers in Endocrinology, 2025)
AimsThis study aimed to investigate the associations between three systemic inflammatory indices, including the systemic immune-inflammation index (SII), systemic inflammation response index (SIRI), and pan-immune-inflammation value (PIV), and the risk of renal function decline in patients with type 2 diabetes mellitus (T2DM).MethodsWe consecutively enrolled 9,537 patients with T2DM hospitalized at Peking University Third Hospital. The systemic inflammatory indices were calculated from baseline blood routine indicators. Renal function decline was defined as an estimated glomerular filtration rate decreasing by ≥ 40% from baseline. All participants were categorized into tertiles according to the systemic inflammatory indices. Restricted cubic spline (RCS) curves, multivariable Cox proportional hazard regression models, and receiver operating characteristic (ROC) curves were used for analysis.ResultsA total of 1,495 outcome events were recorded during the follow-up. The RCS analysis suggested a non-linear association of systemic inflammatory indices with the risk of renal function decline (P for nonlinear < 0.001). Using the lowest tertile as reference, multivariate Cox regression revealed that patients in the highest tertile of the three systemic inflammatory indices had a significantly higher risk of renal function decline (SII: HR=1.67, 95% CI=1.47–1.91, P<0.001; SIRI:HR=1.69, 95% CI=1.46–1.95, P<0.001; PIV: HR=1.58, 95% CI=1.38–1.81, P<0.001). The ROC curves showed that the SIRI was better than other two indices at predicting renal function decline.ConclusionA significantly positive association was shown between systemic inflammatory indices and the risk of renal function decline in T2DM patients. Among these inflammatory indices, SIRI has relatively high predictive performance for renal function decline.